2005
DOI: 10.1083/jcb.200507048
|View full text |Cite
|
Sign up to set email alerts
|

The vacuolar DHHC-CRD protein Pfa3p is a protein acyltransferase for Vac8p

Abstract: Palmitoylation of the vacuolar membrane protein Vac8p is essential for vacuole fusion in yeast (Veit, M., R. Laage, L. Dietrich, L. Wang, and C. Ungermann. 2001. EMBO J. 20:3145–3155; Wang, Y.X., E.J. Kauffman, J.E. Duex, and L.S. Weisman. 2001. J. Biol. Chem. 276:35133–35140). Proteins that contain an Asp-His-His-Cys (DHHC)–cysteine rich domain (CRD) are emerging as a family of protein acyltransferases, and are therefore candidates for mediators of Vac8p palmitoylation. Here we demonstrate that the DHHC-CRD p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
91
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(96 citation statements)
references
References 40 publications
(66 reference statements)
3
91
1
Order By: Relevance
“…Also, deletion of ERF2 still permits partial Ras2 palmitoylation and localization (33), and our data suggest that some Vac8 is palmitoylated in pfa3⌬ cells. In agreement with this postulate, Linder and colleagues (28) detected residual palmitoylation of Vac8 by metabolic labeling with [ 3 H]palmitate in pfa3⌬ cells. The localization of Vac8 to pfa3⌬ vacuoles is in striking contrast to the poor binding of a Vac8 mutant that lacks its N-terminal cysteines and thus cannot be palmitoylated (K.S., L.E.P.D., H.H., T.J.L., and C.U., unpublished work).…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Also, deletion of ERF2 still permits partial Ras2 palmitoylation and localization (33), and our data suggest that some Vac8 is palmitoylated in pfa3⌬ cells. In agreement with this postulate, Linder and colleagues (28) detected residual palmitoylation of Vac8 by metabolic labeling with [ 3 H]palmitate in pfa3⌬ cells. The localization of Vac8 to pfa3⌬ vacuoles is in striking contrast to the poor binding of a Vac8 mutant that lacks its N-terminal cysteines and thus cannot be palmitoylated (K.S., L.E.P.D., H.H., T.J.L., and C.U., unpublished work).…”
Section: Discussionsupporting
confidence: 55%
“…Pfa3 is required for efficient Vac8 localization to vacuoles, consistent with its ability to promotes palmitoylation in vitro upon reconstitution (28). Loss of Pfa3 leads to partial mislocalization of Vac8 to the cytosol and a reduction in vacuole fusion.…”
Section: Discussionmentioning
confidence: 83%
“…For the quantitation presented in Fig. 2C, soluene extraction of the protein of interest was performed as described previously (26,29). For the quantitation presented in Figs.…”
Section: Methodsmentioning
confidence: 99%
“…The N-terminal cysteines, and presumably the palmitoylation that occurs there, are required for the function of Vac8 in vacuolar fusion and vacuolar inheritance (18,24,25). We recently demonstrated both genetically and biochemically that the yeast DHHC protein Pfa3 is a Vac8 PAT (26).…”
mentioning
confidence: 99%
“…In contrast to other acyl transferases that are soluble, the DHHCs are multi-membrane-spanning domain-containing proteins with the catalytic motif facing the cytosol (Mitchell et al, 2006). Site-directed mutagenesis established a direct involvement of the DHHC motif in palmitate transfer, since substitution of the cysteine residue was enough to abolish both autopalmitoylation of the PAT and palmitoylation of substrates (Roth et al, 2002;Smotrys et al, 2005). It was recently clearly demonstrated that the auto-palmitoylated PAT serves as a covalent intermediate between the donor palmitoyl-CoA and the acceptor in a two-step process (Jennings and Linder, 2012).…”
Section: Enzymes Implicated In Protein Palmitoylationmentioning
confidence: 99%